SYMBOLISM IN ALEXANDER PUSHKIN’S THE QUEEN OF SPADES SHORT STORY - Dina Friskaliana; Singgih Daru Kuncara; Anjar Dwi Astuti (Fakultas Ilmu Budaya Universitas Mulawarman, 2020)
This study examines the symbols that used, the meanings of symbol, and the roles of symbol in The Queen of Spades short story. To identify the symbol, the researcher used the theory by Griffith; public symbol and private symbol. To reveal the meanings of symbol, the researcher used the theory of ‘symbolic reference’ by Whitehead. Then, to find out the roles of symbol in building the story, the researcher analyzed through plot, character, setting, and theme in the story. The method of this study used descriptive qualitative method and the data of this study based on words, sentences, and narration which reflected symbols throughout the story. Furthermore, the result of the research showed cards of three, seven, aces categorized as public symbol and the queen of spades categorized as private symbol. The number three reflected to love triangle which happened between Hermann, Lizaveta, and Lizaveta’a husband. Then, seven reflected Hermann who obsessed to know the secret of lucky card. At last, aces reflected to karma that must be accepted by Hermann and the Countess. Meanwhile, the queen of spades as private symbol reflected to the Countess Anna Fedotovna and as a symbol of the key issue on the secret of lucky cards in the story. Then, the roles of symbols reflected through plot that showed to express the disquieting effect, character that showed to express the strength qualities, setting that showed to express the strength atmosphere, and theme that showed to express the wisdom lessons.